Instituitional isormorphism in financial disclosure practices in Malaysian local government - Teruki, Neilson (Asian Academic Research Associates, 2017)
The role of organisational and environmental factors in determining financial disclosure practices has so far not been adequately addressed. Neither has there been any attempt to carry out field studies to analyse financial disclosure practices within a particular organisation. Therefore, no serious efforts have been made to link the effects of institutional and social aspects with the quality of mandatory disclosures in firms‘ financial statements. Consequently, there is a need to conduct a study to examine the financial disclosure practices and management in the public sector, taking into account various organisational, social, and environmental factors. These factors are expected to have an influence on the manager‘s decision to disclose information. Thus, the aim of this paper is to gain knowledge and understanding on the financial disclosure practices and management in Malaysian Local Authorities (MLAs). More specifically, this study seeks to investigate the factors taken into consideration when determinations are made relating to financial disclosure, the functions of auditor (s) and other parties, and the impact of external disclosure rules on the process of decision-making pertaining to disclosures. In terms of methodology, this study adopts a case study approach by using semi-structured interviews and conducting review of internal documents. The fieldwork consists of holding interviews with 30 individuals who come from various backgrounds, and who worked at different levels and held different positions in six MLAs, together with document analysis. It was found that there is the existence of coercive, normative, and mimetic isomorphism in MLAs‘ disclosure practices. The isomorphism comes from mimetic rules (regulations and legislations, pressure from state authority), normative rules (professionalization), as well as mimetic rules (disclosure practices of other councils, and the influence of external auditor).